PARADOKS DIALOG LINTAS IMAN (PARADOX OF INTERFAITH DIALOGUE) - , VICKY DIAN PRATAMASARI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The study aims to understand and describe comprehensively the form of dialogue which is built by the Forum of Yogyakarta Brotherhood of Believers (FPUB) and examine the impact along with Turgoâs society toward the dialogue forum. The research is conducted in Turgo a hamlet, Purwobinangun village, Pakem, Sleman, Yogyakarta. FPUB builds Suropanggah bridge as a media in realizing the interfaith dialogue in the form of âdialog karyaâ. During the process of preparation and implementation, the research method used was a case study with a qualitative approach. The Case study used in this study aimed to observe the construction of the model of religious âdialog karyaâ in Turgo which is the specific work area of FPUB. Meanwhile, the techniques of data collection are done by observation, in-depth interviews, field documentation, and literature studies. The results of this study indicate that the presence of FPUB considered be able to neutralize the tensions between religious relations in Turgo by installing the interfaith tolerance that âwe are a brotherâ who demands respect and protect each other, not only neighbors. Nevertheless, due to the crush of spatial Merapi Eruption (1994) and developed by the network pattern variations FPUB bring construction to a religious dialogue. Response and adaptation of religious elites tend to be more varied as there are positive and negative responses. While the response and adaptation of religion mass tend to be the same. Variations of response and adaptation of the elite and the masses of Islam, Christianity, and Catholicism show that there are various meanings given to their experiences that influence the difference reflection in the form of action. The infrastructure development gives more impressive meaning in creating the interfaith harmony compare to the dialogue in the form of forums discussion. Look for similarities and differences among religious believers in the frame of intellectual discourse are intangible for the vision attainment of peace in the interfaith dialogue. Implementation in the form of real action is the only way that afford to cross the formal boundaries with humanitarian principles as its starting point which is often not able to be achieved by dialogue in the form of forums discussion.